POD13 White matter connectivity in semantic dementia. Issue 11 (22nd October 2010) - Jones, M; Neary, D; Embleton, K; Snowden, J; Herholz, K
Abstract : Semantic Dementia (SD) is known to be associated with grey matter atrophy of the anterior temporal lobes (ATL). The effect of the disease on white matter fibres has been less extensively studied. Semantic knowledge is thought to be organised in a widely distributed network throughout the brain connected by a number of white matter bundles. We explore the white matter connectivity of the semantic network in subjects with SD and healthy controls. Six subjects with SD and four healthy controls underwent diffusion weighted MR tractography imaging. Region of interest placement was performed to allow reconstruction of specific tracts thought to be involved in the semantic network and other classical language pathways. Tracts were assessed by visual inspection and quantitative atlas based region of interest analysis. SD subjects had a significantly reduced pattern of white matter connectivity from the left ATL. Specific tract reconstructions demonstrated significant reductions in connectivity in the left uncinate, inferior fronto-occipital fasciculi and anterior commissure tract in SD subjects. The arcuate fasciculi did not appear different between groups. The results demonstrate that in SD there is disruption of the semantic network extending beyond the boundaries of the ATLs and involving specific white matter pathways.